Environmental conditions in commercial restaurants of a public university - Marlene Azevedo Magalhães Monteiro; Cynthia Graciane Carvalho Ramos; Rita de Cássia Ribeiro; Maria Aparecida Vieira Teixeira Garcia (O Mundo da Saúde)
The aim in this study was to assess environmental working conditions in commercial restaurants located in a public teaching institution in Belo Horizonte-MG, Brazil. Lighting and noise levels were assessed in the product reception sector, lunchroom, meals production and food storage areas of four restaurants. Lighting and noise levels were collected with the help of a lux meter and a decibel meter, at one-hour and 20-minutes intervals, respectively, from 08h00min to 12h00min, during three non-consecutive days. In addition, an interview was held with sixty employees based on the Occupational Ergonomics Analysis Questionnaire. At all restaurants, lighting levels were below recommendations for the production reception sector, and the restaurant A, regarding for meal production. The storage sectors and the cafeteria had adequate light intensity. Noise levels were adequate, ranging from 55.5 to 85.7dB. Employees classified their work as physically hard (47.1%, n = 28), and 33.3% (n = 20) reported that the environmental working conditions causes fatigue and/or irritation and 86.2% (n = 525) indicate insufficient space to move. The restaurants assessed presented inappropriate environmental work conditions, which can interfere in productivity and occupational health.